2017
DOI: 10.5812/aapm.44732
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Systemic Lidocaine in the Management of Chronic Pain: A Literature Review

Abstract: ContextDespite recent advances in the understanding of the chronic pain concept, its diagnosis and management remains a daily challenge for clinicians and patients. Based on the published literature, this review discusses and tries to organize the current knowledge and the up-to-date clinical experience about the efficacy and safety of the use of intravenous lidocaine in treatment and prevention of chronic pain.Evidence AcquisitionTo prepare this narrative review, we performed an in depth literature review usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…In addition, intravenous lidocaine may inhibit G protein-coupled receptors, N-methyl-D-aspartate receptors, the release of inflammatory factors and the function of leukocytes. Therefore, it has anti-inflammatory, analgesic, anti-hyperalgesic and immune regulatory effects (33)(34)(35)(36). A previous study indicated that the major mechanism of the anaesthetic action of propofol is the inhibition of sodium channels in the central nervous system, and lidocaine is able to enhance the effect of propofol by also inhibiting sodium channels (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intravenous lidocaine may inhibit G protein-coupled receptors, N-methyl-D-aspartate receptors, the release of inflammatory factors and the function of leukocytes. Therefore, it has anti-inflammatory, analgesic, anti-hyperalgesic and immune regulatory effects (33)(34)(35)(36). A previous study indicated that the major mechanism of the anaesthetic action of propofol is the inhibition of sodium channels in the central nervous system, and lidocaine is able to enhance the effect of propofol by also inhibiting sodium channels (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that perioperative infusion of lidocaine may also have an analgesic effect by affecting postoperative serum concentrations of endocannabinoids, N-acylethanolamines (NAE) and endogenous opioids: β-endorphin, enkephalin and dynorphin [28,29]. Numerous studies and meta-analyzes have shown a positive effect of the perioperative systemic lidocaine administration in adults on the postoperative analgesia, gastrointestinal recovery and duration of hospitalization in major surgery [9,10,13,17,21,30]. However recent meta-analyzes suggest that lidocaine exerts a positive analgesic effect only in abdominal surgery [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that lidocaine also beneficially supplements therapy aiming at improving patient comfort in the postoperative period [9][10][11][12][13][14][15][16][17]. However, there are no studies evaluating the intravenous (i.v) lidocaine as an element of analgesic multimodal therapy in spine surgery in children.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetics, such as systemic lidocaine, have shown benefit in chronic pain by decreasing hyperalgesia and inflammatory response. 65 While systemic lidocaine has a large quantity of evidence for use, it exists mostly for chronic neuropathic pain syndromes, including postherpetic neuralgia and chronic low back pain secondary to osteoarthritis, and has less evidence for use in acute or nociceptive pain. 65 Sys-temic lidocaine also has inflammatory properties that exceed those of other commonly used anti-inflammatories, with many fewer adverse effects.…”
Section: Anestheticsmentioning
confidence: 99%
“…65 While systemic lidocaine has a large quantity of evidence for use, it exists mostly for chronic neuropathic pain syndromes, including postherpetic neuralgia and chronic low back pain secondary to osteoarthritis, and has less evidence for use in acute or nociceptive pain. 65 Sys-temic lidocaine also has inflammatory properties that exceed those of other commonly used anti-inflammatories, with many fewer adverse effects. This has gained lidocaine popularity for treating other, more difficult, chronic pain syndromes, such as complex regional pain syndrome (CRPS) and fibromyalgia.…”
Section: Anestheticsmentioning
confidence: 99%